Taxing Multinational Enterprises: A Theory-Based Approach to Reform - Wolfram F. Richter (Center for Economic Studies and ifo Institute (CESifo), 2022)
Almost 140 countries have agreed to reallocate the rights to tax international corporate profits and to introduce minimum tax rates. The agreed plan is the product of pragmatism and a search for consensus, but ambitious. It includes steps towards unitary taxation to be established by a multilateral convention that the world has not yet seen in comparable format. This paper argues for a reform that retains separate entity accounting and addresses the flaws in the current system of corporate taxation at their root rather than merely fixing symptoms. To this end, a reform aimed specifically at the rules governing the taxation of intangible assets is recommended.
Keywords: H25; F23; M48; 330; OECD/G20 BEPS Project; formula apportionment; separate entity accounting; Shapley assignment of taxing rights; residual profit allocation/splitting